Hold Relax dan Passive Stretching Efektif Dalam Meningkatkan Kemampuan Fungsional Pada Pasien Post-Gips Fracture Tibial Plateau Dextra - Nizatul Mumtazah; Faizah Abdullah Djawas (LPPM Universitas Abdurrab, 2020)
Background: Tibial plateau fracture is one type of fracture that usually occur in legs. Tibial Plateau fracture usually occur because of high energy trauma that produced by the force of varus and valgus and also because of axial loading or because of the pedestrian that crashed by the car with high energy which can also called as fracture bumber. The purpose of this case study is to examine the effectiveness of hold relax and passive stretching in tibial plateau fracture. Method: A single case study, providing physiotherapy interventions for a 44 year old woman with a diagnosis of a tibial plateau post-cast fracture. Hold-relax stretching is a technique in which shortened antagonistic muscle groups are isometrically contracted against the optimal resistance given by the physiotherapist. Passive stretching is a method for extending the contractile or non-contractile components of the musculotendinoeus unit where force is exerted externally and given manually. Hold relax and passive stretching are given for 2 weeks with 5 evaluations. ROM assessment was measured by a goniometer and spasm by palpation. Result: There is an increase in LGS knee flexion 90á´¼ to 110á´¼ and decrease in spasm which associated with an improvement LEFS score from 17 to 44, indicates that there is an increase in the functional ability of lower extremity. Conclusion: This study shows that the method of therapeutic exercise with hold relax and passive stretching can improve functional ability in tibial plateau fracture which is measured using LEFS parameters.